Copies of the treaties (1 and 2) made 3rd and 21st August, 1871 between Her Majesty the Queen and the Chippewa and Cree Indians of Manitoba and country adjacent [electronic resource]. - Ojibwa Indians. Treaties, etc. 1871.; Cree Indians. Treaties, etc. 1871.; Canada. Treaties, etc. 1871. ([Ottawa? : s.n.], 1879)
Electronic reproduction. Mode of access: Internet. 44